The influence of 2D MoS2 layers on the growth of GaN films by plasma-assisted molecular beam epitaxy - Susanto, Iwan; Tsai, Chi-Yu; Fachruddin; Rahmiati, Tia; Ho, Yen-Ten; Tsai, Ping-Yu; Yu, Ing-Song (My University, 2019)
In the report, the growth of GaN films on the two-dimension molybdenum disulfide (2D MoS2) and c-sapphire via plasma-assisted molecular beam epitaxy (MBE) was investigated. Two kinds of MoS2 layers were prepared by pulsed laser deposition (PLD) and chemical vapor deposition (CVD) techniques. Three different surface conditions were designed for the growth of GaN films. GaN thin films in the form of polycrystalline were successfully grown on the surface of MoS2 layers. From the surface analysis, CVD technique provided an amorphous and rougher MoS2 surface for the MBE growth. On the contrary, PLD supplied a better in-plane and smoother surface for GaN growth which included more stability of surface chemical composition, higher crystallinity and better near-band-edge emission property. To compare with the growth on c-Sapphire, however, the van der Waals expitaxial growth of single-crystalline GaN films on sp(2) bonded 2D MoS2 is still a challenge. The growth of GaN films on sp(3) bonded c-sapphire still performed the best results in the report. In summary, we demonstrate better growth of GaN thin films on 2D MoS2 surface provided by PLD. The hetetrostructure of 3D GaN on 2D MoS2 semiconductors could be useful in the future applications of electronic and optoelectronic devices.
Keywords: Molecule beam epitaxy; Gallium nitride; Molybdenum disulfide; Pulsed laser deposition; van der Waals epitaxy